Neutralization of Interleukin 1-beta is associated with preservation of thalamic capillaries after experimental traumatic brain injury - Özen, Ilknur; Clausen, Fredrik; Flygt, Johanna; Marklund, Niklas; Paul, Gesine (Frontiers in Neurology, 2024)
Traumatic brain injury to thalamo-cortical pathways is associated with post-traumatic morbidity. Diffuse mechanical forces to white matter tracts and deep grey matter regions induce an inflammatory response and vascular damage resulting in progressive neurodegeneration. Pro-inflammatory cytokines, including interleukin-1β (IL-1β), may contribute to the link between inflammation and the injured capillary network after TBI. This study investigates whether IL-1β is a key contributor to capillary alterations and changes in pericyte coverage in the thalamus and cortex after TBI. Animals were subjected to central fluid percussion injury (cFPI), a model of TBI causing widespread axonal and vascular pathology, or sham injury and randomized to receive a neutralizing anti-IL-1β or a control, anticyclosporin A antibody, at 30 min post-injury. Capillary length and pericyte coverage of cortex and thalamus were analyzed by immunohistochemistry at 2-and 7-days post-injury. Our results show that early post-injury attenuation of IL-1β-dependent inflammatory signaling prevents capillary damage by increasing pericyte coverage in the thalamus.